Success principles how to get from where you are to where you want to be - Canfield, Jack; Switzer, Janet 1953- (New York Harper Resource Book, 2005)
A self-improvement guide for business professionals, teachers, students, parents, or anyone interested in promoting themselves within today's success-oriented culture shares sixty-four practical or inspiring principles on how to reach desired goals. Get ready to transform yourself for success. Jack Canfield, co-creator of the phenomenal bestselling Chicken Soup for the Soul series, turns to the principles he has studied, taught, and lived for more than 30 years in this practical and inspiring guide that will help any aspiring person get from where they are to where they want to be. The Success Principles will teach you how to increase your confidence, tackle daily challenges, live with passion and purpose, and realize all your ambitions. Not merely a collection of good ideas, this book spells out the 64 timeless principles used by successful men and women throughout history. And the fundamentals are the same for all people and all professions -- even if you're currently unemployed. It doesn't matter if your goals are to be the top salesperson in your company, become a leading architect, score straight A's in school, lose weight, buy your dream home, or make millions of dollars-the principles and strategies are the same. From learning these basics, you can then tackle the important inner work needed to transform yourself. After this inner work, you can turn to building a "success team" and the important ways of transforming your relationships for lasting success. Finally, because success always includes a financial dimension, you can learn to develop a positive money consciousness along with the habits that will ensure that you have enough to live the lifestyle you want, while keeping the importance of tithing and service central to your financial practice. Taken together and practiced every day, these principles will transform your life beyond your wildest dreams! Filled with memorable and inspiring stories of CEO's, world-class athletes, celebrities, and everyday people, The Success Principles will give you the courage and the heart to start living the principles of success today. Go for it!
The fundamentals of success -- Transform yourself for success -- Build your success team -- Create successful relationships -- Success and money -- Success starts now.
Includes bibliographical references (p. [441]-451) and index.
86202
Keywords: Success -- Psychological aspects